An inadvertent missiologist: Edward Gibbon and the science of mission. (January 2016) - Skreslet, Stanley H.
Edward Gibbon unintentionally inaugurated the science of mission ( Missionswissenschaft ), when he published in 1776 the first volume of his celebrated History of the Decline and Fall of the Roman Empire . Gibbon included in his groundbreaking work a new approach to mission history that emphasized social analysis and cultural change, rather than theology. Gibbon's secular discourse on the establishment, growth and "triumph" of early Christianity over paganism is highly critical of the faith, in line with his own stance of religious skepticism, but is insightful nevertheless, as he shows how the study of mission from a sociological perspective can shed light on the social processes that often shape evangelistic outcomes. In the Decline and Fall, Gibbon also defined a style of speaking or a discourse about Christian mission that has come to dominate the secular academy today.